2021
DOI: 10.1080/24750263.2021.1889054
|View full text |Cite
|
Sign up to set email alerts
|

Under-ice environmental conditions, planktonic communities and ichthyofauna in dystrophic lakes

Abstract: High content of humic substances and low pH values are factors limiting the species richness and abundance of some organisms in dystrophic lakes. Unfavourable winter conditions (i.e. low water temperature, poor light conditions, ice/snow cover) may additionally restrict their development. The aim of this study was to compare ice-on (winter) and ice-off (summer) abiotic (organic carbon, total phosphorus and nitrogen) and biotic (chlorophyll a, phytoplankton, ciliates, rotifers, crustaceans, fish) parameters in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The maximum depth of the lakes ranged from 3.5 to 8 m (Table 1 ). The biomass and the number of fish species were very low in the studied lakes 25 , 48 . Dystrophic conditions were evaluated by the hydrochemical dystrophy index (HDI), which uses data on surface water pH, electric conductivity, and DIC/DOC ratio 4 .…”
Section: Methodsmentioning
confidence: 86%
See 2 more Smart Citations
“…The maximum depth of the lakes ranged from 3.5 to 8 m (Table 1 ). The biomass and the number of fish species were very low in the studied lakes 25 , 48 . Dystrophic conditions were evaluated by the hydrochemical dystrophy index (HDI), which uses data on surface water pH, electric conductivity, and DIC/DOC ratio 4 .…”
Section: Methodsmentioning
confidence: 86%
“…On the other hand, the high biomass of phytoplankton contrasts with the low biomass of zooplankton in dystrophic lakes, which results in low efficiency of the transfer of matter and energy in planktonic food webs 20 22 . Furthermore, dystrophic lakes are unproductive from a fishery point of view, with low fish densities or an absence of fish 23 25 . Thus, a large amount of food and low fish pressure in temperate humic lakes usually do not lead to the mass development of large-bodied zooplankton, and the limiting factors for zooplankton growth are unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Species of genera Ascomorpha and Polyarthra prefer acidic environments (Rybak 1994). Other studies performed in dystrophic water bodies reported occurrence of the same genera, for example, Polyarthra, Lecane, Colurella and Trichocerca (Demetraki-Paleolog and Kolejko 2011);Polyarthra, Trichocerca and Keratella cochlearis (Kuczyńska-Kippen 2008); Asplanchna, Colurella, Lecane, Polyarthra and K. cochlearis (Demetraki-Paleolog et al 2018); Polyarthra, Trichocerca, K. cochlearis and Asplanchna (Karpowicz and Ejsmont-Karabin 2018); Ascomorpha, Trichocerca, K. cochlearis and Asplanchna (Kalinowska et al 2021); and Ascomorpha, Asplanchna, Colurella and Polyarthra (Quiroga et al 2013). These studies also reported other genera that were not noted in the reservoir studied.…”
Section: Planktonic Rotifersmentioning
confidence: 86%
“…According to a literature review, the abundance and composition of plankton in post-peat reservoirs remain understudied (Mieczan 2007;Demetraki-Paleolog and Kolejko 2011). Similar studies in dystrophic lakes are more advanced and are concentrated on the impact of environmental parameters on phytoplankton or zooplankton distribution (Karpowicz and Ejsmont-Karabin 2018;Lebret et al 2018;Kalinowska et al 2021). Kalinowska et al (2021) emphasised that majority of studies in dystrophic lakes are carried out during the growing season and the winter planktonic communities are less thoroughly studied.…”
Section: Introductionmentioning
confidence: 99%